2019
DOI: 10.1002/nau.24205
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 2 activation decreases severity of cyclophosphamide‐induced cystitis via regulating autophagy

Abstract: Purpose: Cannabinoids have been shown to exert analgesic and anti-inflammatory effects, and the effects of cannabinoids are mediated primarily by cannabinoid receptors 1 and 2 (CB1 and CB2). The objective of this study was to determine efficacy and mechanism of CB2 activation on cyclophosphamide (CYP)-induced cystitis in vivo. Methods: Cystitis was induced by intraperitoneal (IP) injection of CYP in female C57BL/6J mice. Mice were pretreated with CB2 agonist JWH-133 (1 mg/kg, intraperitoneally), CB2 antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Furthermore, Liu et al (2020a) showed that JWH133 diminished mechanical hyperalgesia, reduced urine spot numbers, and enhanced the micturition frequency mediated by cyclophosphamide-induced cystitis in mice. They also observed a reduction in bladder tissue inflammation and oxidative damage as indicated by reduced levels of proinflammatory mediators, including IL-1β, TNF-α, and IL-8, and enhanced activities of cellular GSH and SOD, while lowering MDA levels.…”
Section: Interstitial Cystitis/bladder Pain Syndromementioning
confidence: 99%
“…Furthermore, Liu et al (2020a) showed that JWH133 diminished mechanical hyperalgesia, reduced urine spot numbers, and enhanced the micturition frequency mediated by cyclophosphamide-induced cystitis in mice. They also observed a reduction in bladder tissue inflammation and oxidative damage as indicated by reduced levels of proinflammatory mediators, including IL-1β, TNF-α, and IL-8, and enhanced activities of cellular GSH and SOD, while lowering MDA levels.…”
Section: Interstitial Cystitis/bladder Pain Syndromementioning
confidence: 99%
“…No changes in the expression of CBR2 were reported in the mouse bladder in cyclophosphamide-induced cystitis (Liu et al, 2020). These discrepancies may be due to species differences and/or the method of induction of cystitis.…”
Section: Cannabinoids and Cystitismentioning
confidence: 92%
“…Whether this is due to reduced inflammation or direct effects on bladder afferents, or both is not clear. A growing body of evidence indicates that CBR2 activation decreases infiltration of inflammatory cells and markers such as leukocytes, interleukins, and tissues necrosis factors in cystitis (Rice et al, 2002;Tambaro et al, 2014;Wang et al, 2014;Liu et al, 2020). This suggests that a reduction in inflammation itself by CBR2 activation may be one of the main causes for a reduction in inflammatory hyperalgesia.…”
Section: Cannabinoids and Cystitismentioning
confidence: 99%
See 2 more Smart Citations